Evaluation of Antioxidant Polyphenols in Taiwan's Medicinal Plants - Shieh, Po-Chuen; Agoramoorthy, Govindasamy; Kuo, Daih-Huang (Asian Journal of Chemistry, 2010)
In this paper, 23 forest plants collected from the lowland subtropical rainforest habitat in southern Taiwan were evaluated to determine total polyphenol content and antioxidant activity (by 2,2-diphenyl-1,1-picrylhydrazyl DPPH free radical scavenging assay against α-tocopherol). The contents of polyphenols in 23 dry plant materials ranged from 2.5 to 164 mg/g in which top 10 is in the order of Acacia confuse, Macaranga tanarius, Euphoria longana, Mangifera indica, Ficus wightiana, Lantana camara, Pittosporum pentandrum, Leucaena lencocephala, Ficus septica and Pittosporum pentandrum. Except for Anredera cordifilia, Ophiopogn japonicus and Setaria palmifolia, other plants are able to eliminate significantly DPPH in 0.5 h indicating that the analyzed plants possess free radical scavenging activity. Our research indicates that Taiwan's lowland subtropical rainforest plants have great potential in scavenging free radicals and the plants can be a vital source of antioxidant phytochemicals.